Academization of bandura by bandurism exponents in Ukraine - Zinkiv, Iryna Ya. (Linguistics and Culture Review, 2021)
Ukrainian bandura underwent a long and difficult evolutionary path. Its academicization process took place in the XX-XXI centuries. The impact of prominent bandura craftsmen O. Korniievskyi, V. Tuzychenko, I. Skliar, and V. Herasymenko on the process of the Ukrainian bandura academization was studied. The authors devoted their work to historical assessment in the affirmation of the academized instruments of Chernihiv (or Kyiv-Chernihiv) and Kharkiv types. The specifics of the creation of the academized instrument in 1920–2010 by leading Ukrainian designers – bandura craftsmen became a purpose of the study. The abovementioned bandura craftsmen made a significant impact on the academization of diatonic banduras, their transformation into the instrument with a double-diatonic tuning system and bringing it closer to European trends. The particular roles of O. Korniievskyi, V. Tuzychenko, I. Skliar, and V. Herasymenko in this process were characterized. It was noted that the Kyiv method of play on an academic instrument is much more popular than Kharkiv-type which is why the latter needs additional attention.